ENVIRONMENTAL MANAGEMENT STRATEGY FOR SHAH ALAM SOLID WASTE TRANSFER STATION, MALAYSIA - B. M, Firuza; I., Nather Khan (Malaysian Journal of Science, 2011)
Waste Transfer stations are the integral part of municipal solid waste management. They essentially function as transit waste collection centres enroute to the landfill facility. The Shah Alam solid waste transfer station (SATS) is the first such transfer station to be established at the industrial zone in the city of Shah Alam. The SATS will be designed to receive approximately 1500 tonnes of municipal solid waste daily. The station will have the capacity to expand its waste reception to approximately 2500 tonnes/day. The key environmental components of concerns during implementation of SATS were air quality, odour, noise, vibration, river water quality, aquatic ecology, socio-economy and traffic and transportation issues around the project area. The baseline data has been collected for the above environmental component and discussed in detail in the existing environmental section of EIA report. Subsequently, the potential environmental impacts arising from the construction and operational phases of the SATS are evaluated based on prevailing regulatory requirements and environmental best management practices. Finally, an Environmental Management Plan (EMP) for the SATS was necessary to effectively manage all the potential impacts identified in this report and monitor the activities at the project site during construction and operational phases of the project. This is to ensure that the environmental objectives are met and all activities relating to the implementation of the project are carried out in an environmentally sustainable manner.